Ferrihydrite sulfidation transformation reduces the mobilization of coexisting cadmium under anoxic conditions: Insights into the transformation mechanism - Xiaoming Zhao; Yifei Wang; Yu Song; Xu Ma; Ning Chen; Leo Ka Long Cheung; Ayetullah Tunc; Reza Deevsalar; Jinru Lin; Yuanming Pan; Haibo Li (Hydrometallurgy, 2026)

Bamboo expansion into broadleaf forests restructures topsoil carbon, nitrogen, phosphorus and potassium pools: A trade-off between carbon sink enhancement and nutrient limitation - Qiudi Wu; Xin Wang; Bing Ma; Hongwei Zhou; Chenyang Huang; Liangjie Wang; Youjin Yan; Ziqiang Liu; Lina Mei; Haibo Hu; Lin Chen; Fengling Gan; et al. (CATENA, 2026)

The Evaluation Method of Flow and Temperature Field for a Subsea Cage-Type Choke Valve - Wujun Tong; Yingying Wang; Zeqing Lin; Dingwen Huang; Haibo Li; Xinzhong Li (Journal of Marine Science and Engineering, 2026)
As a critical regulating component in subsea Christmas tree systems, the cage-type choke valve governs the overall production efficiency and operational reliability of offshore oil and gas exploitation owing to its unique internal flow field characteristics. In accordance with the in situ operating conditions of the target oilfield, this paper performs a numerical simulation and systematic analysis on the flow field behaviors of a cage-type choke valve. Based on the fundamental theories of computational fluid dynamics (CFD), a three-dimensional coupled flow and heat transfer numerical model for the target choke valve is constructed via the FLUENT solver. Flow parameters under diverse pressure difference conditions are measured, validating the accuracy and feasibility of the established numerical model. Corresponding model hypothesis criteria and boundary condition configuration schemes are explicitly defined. Spatial distribution characteristics of the internal temperature, velocity, and pressure fields of the choke valve under different operating conditions are obtained through numerical simulation. Ten monitoring nodes uniformly arranged along the fluid domain from the inlet to the outlet are selected for quantitative analysis. The research results clarify that lower seawater temperature intensifies heat dissipation, leading to the observed temperature decrement, and confirm that the cage orifice structure dominates the flow acceleration, with the pressure drop magnitude linearly correlating with the inlet–outlet differential pressure. The research methodology and numerical findings of this study can provide a reliable basis for structural optimization and operating condition matching of cage-type choke valves applied in subsea oil and gas production systems.

Multi-level optimized displacement field reconstruction in icebreaker structures using inverse finite element method - Sen Wan; Meng Zhang; Lin Ren; Zhaochun Zhang; Donghui Wang; Ding Chen; Xiaohui Zhang; Haibo Hu; Nan Li (Ocean Engineering, 2026)

Fe2+ alters carbon and nitrogen metabolic networks in a composite microbial consortium: Metagenomic insights into the shift from denitrification to DNRA - Lin Zhang; Bowei Zhao; Xiao Zhang; Yuan Li; Haibo Li; Shuying Yuan; Haoxiang Ning; Bingcheng Lv; Le Li; Xiaojun Fan; Xiuping Yue (Environmental Research, 2026)

A Pt/h-Co-Nc nanozyme hydrogel air-fuel cell mediating cascade DNA walking for point-of-care detection - Ning Li; Lin Sun; Kaili Wang; Lihui Mao; Xuecai Tan; Haibo Wang; Ke-Jing Huang; Shaogang Liu (Chemical Engineering Journal, 2026)

Dynamic disruption of interfacial hydrogen-bond networks via orbital engineering for accelerated alkaline hydrogen evolution - Juping Wang; Hongyue Diao; Zexing Wu; Weiping Xiao; Qi Wu; Tianyi Ma; Nan Lin; Haibo Lin; Lei Wang (Chemical Engineering Journal, 2026)

Cl−-repelling Mn3O4/Co(OH)2 heterojunction on self-supporting N-doped CNTs for high-stability seawater zinc-air batteries - Lin Mu; Yuxin Yao; Haibo Zhao; Shifang Yang; Ying Wang; Peng Yu (Chemical Engineering Journal, 2026)

Injectable icaritin-loaded Pickering emulsion gel for overcoming immunotherapy resistance in malignant ascites - Huijuan Wei; Jing Wang; Lin Zhong; Jia Zhang; Xuqi Sun; Xuanwen Bao; Haibo Zhang; Dong Chen; Jianhao Liu; Xiaomeng Dai; Peng Zhao (Chemical Engineering Journal, 2026)

Green Synthesis of Magnetic Algae Supported Fe3O4 via MOF Pyrolysis for Efficient UO₂(NO₃)₂ Adsorption - Shiji Lin; Yuantao Chen; Wei Zhang; Chaoli Shao; Haibo Mao; Xiaohang Zhou (Water, Air, & Soil Pollution, 2026)

A stabilized single-sided nonlinear inverse finite element framework for large-deformation displacement field reconstruction - Shiyan Lv; Meng Zhang; Lin Ren; Zhaochun Zhang; Donghui Wang; Ding Chen; Xiaohui Zhang; Haibo Hu; Nan Li (Ocean Engineering, 2026)

Transferable prediction of TBM long-distance tunneling construction duration considering uncertainties in surrounding rock distribution and the evolution of tunneling efficiency - Jianming Zhang; Kebin Shi; Peixuan Lin; Lei Li; Qiyong Mao; Haibo Jiang; Xinjun Yan; Jingwei Gong (Tunnelling and Underground Space Technology, 2026)

Evaluating the Shanghai Typhoon Model against State-of-the-Art Machine-Learning Weather Prediction Models: A Case Study for Typhoon Danas (2025) - Zeyi Niu; Wei Huang; Yuhua Yang; Mengqi Yang; Lin Deng; Haibo Wang; Hong Li; Xu Zhang (Advances in Atmospheric Sciences, 2026)

Nonequilibrium fractionation of rare earth elements during typhoon-induced event sedimentation - Yanbin Fan; Yunhai Li; Yunpeng Lin; Haidong Li; Hengbo Wang; Haibo Fan; Hannv Zhang; Guicai Zhong; Feng Jiang (Frontiers in Marine Science, 2026)
High-energy, short-lived typhoon deposition can disrupt particle–water interactions, raising the question of whether rare earth elements (REEs) in event deposits still reflect equilibrium-controlled partitioning or instead capture transient, non-equilibrium geochemical states. We sampled a ~0.5–1 cm surface storm layer and underlying background sediments at 11 stations in the northeastern Beibu Gulf on 29–30 September 2024 (20–21 days after Typhoon Yagi), and quantified major/trace elements and REEs by ICP-OES and ICP-MS, integrating grain size/TOC and statistical correlations. Storm deposits show systematically lower ∑REE and LREE concentrations and slightly lower LREE/HREE ratios than background sediments, accompanied by weaker negative Eu anomalies and a shift toward slightly negative Ce anomalies relative to the mild positive Ce anomaly in background deposits. Despite finer textures and elevated TOC in the storm deposits, the canonical grain-size/adsorption control collapses, with ∑REE exhibiting little to no correlation with grain-size under storm conditions. Critically, storm deposits display pronounced LREE–HREE decoupling: LREE behave quasi-conservatively with “event-scale inertia”, whereas HREE respond more sensitively to non-equilibrium carrier reorganization and rapid settling. This selective decoupling provides a diagnostic geochemical fingerprint for identifying event-driven sedimentation and highlights the need to incorporate kinetic/time-scale effects when interpreting REE-based proxies in dynamic environments.

Ecological regime shifts weaken sedimentary carbon sequestration in shallow Lake liangzi - Jinglin Hou; Qi Lin; Jiasheng Zhang; Shixin Huang; Yuan Jin; Yanhua Wang; Haibo He; Pierre Taillardat; David Taylor; Ke Zhang; Michael E. Meadows (Water Research, 2026)

Spatiotemporal variability of PAHs and PAEs in sediments driven by hydrological rhythms in Danjiangkou Reservoir, China: Multisource analysis to machine-learning prediction - Li Lin; Lei Dong; Haibo Zhang; Guochuan Yin; Zhuqi Chen; Haiyang Jin; Xingrui Qi; Xiong Pan; Yu Gao (Process Safety and Environmental Protection, 2026)

Pulse electrodeposition of Nd-doped SnO2-based electrocatalysts for enhanced electrochemical production of ozone and active chlorine - Fuchang Duan; Jinglei Si; Xiaoge Peng; Xiaosa Wang; Yang Ding; Wei Guo; Pan Hu; Yanan Deng; Haibo Lin; Haoqiang Cao; Yunyi Cao; Xing Zhong; et al. (Chemical Engineering Journal, 2026)

Mechanisms of quinone-functionalized FeOOH for enhanced nitrogen removal in micro-aerobic activated sludge process treating low carbon-to-nitrogen ratio wastewater - Haibo Li; Lin Zhang; Bowei Zhao; Aijuan Zhou; Xiuping Yue; Xiao Zhang (Bioresource Technology, 2026)

Collaborative mechanism of road traffic exhaust and noise emission: a cellular transmission model based approach - Haibo Wang; Jiahua Sun; Junshan Lin (Air Quality, Atmosphere & Health, 2026)

Autonomous DNA walker-driven bioelectrocatalytic system with spatiotemporal control for ultrasensitive molecular diagnostics - Bei Zhang; DanYao Tang; Lin Sun; Haibo Wang; Jiawen Wu; Yanni Luo; Ke-Jing Huang; Shengyu Xie (Journal of Environmental Chemical Engineering, 2026)

Hydrophobic neutral and basic fractions of organic fertilizer-derived dissolved organic matter promote phosphorus mobilization in paddy soils - Haibo Wang; Xipeng Liu; Songcan Chen; Chengliang Sun; David R. Chadwick; Davey L. Jones; Xianyong Lin (Soil and Tillage Research, 2026)

Hydrothermal extraction and characterization of hemicellulose from biomass as a natural emulsifier - Yilin Li; Shuo Jiang; Zhiyuan Xu; Yixiang Xu; Seunghee Yoon; Xuanbo Liu; Yifan Cheng; Sean F. O'Keefe; Jactone Ogejo; Feng Lin; Yiming Feng; Haibo Huang (Food Chemistry, 2026)

Enhancing capacitive energy storage in Na0.5Bi0.5TiO3-based relaxor ferroelectric ceramics by tuning polymorphic polar nanoregions - Binglong Zheng; Ying Lin; Fei Yan; Qibin Yuan; Yongzhen Ma; Yanlong Ma; Yu Zhang; Da Li; Haibo Yang (Chemical Engineering Journal, 2026)

Impact of low-emission driving behavior on brake wear PM emissions: insights from a real-world evaluation - Ye Liu; Tangjian Wei; Haibo Chen; Sijin Wu; Yili (Kelly) Tang; Zhiyuan Lin; David Watling; Jingwen Yao; Nansong Yue; Chenxi Wang; Dingsong Cui; Dimitris Margaritis (Transportation Research Part D: Transport and Environment, 2025)

Biocontrol efficiency and potential mechanism of dimethyl trisulfide against postharvest Diplodia stem-end rot in pummelo (Citrus maxima) - Yankun Lin; Shun Feng; Haijin Cai; Haibo Wang; Xiuli Zhang; Fangfang Wu; Shuoyu An; Xinguo Li (Postharvest Biology and Technology, 2025)

Electrode interfacial wettability engineering for high-efficiency synthesis of dimethyl sebacate via Kolbe electrolysis - Linchuan Cong; Xinxin Li; Fuyu Han; Yupeng Wu; Kewen Ma; Ciduo Wang; Nan Lin; Haibo Lin (Chemical Engineering Journal, 2025)

Techno-economic analysis of cost-competitive hard carbon production from biomass for sodium-ion batteries - Yilin Li; Yixiang Xu; Yifan Cheng; Sean F. O’Keefe; Jactone Ogejo; Feng Lin; Haibo Huang (Bioresource Technology, 2025)

Smartphone-assisted Ce-POM/CuBTC peroxidase-like colorimetric detection of H2O2 and ascorbic acid in food samples - Yiyi Zhang; Haibo Zhang; Chengyuan Ma; Yihang Yang; Xuan Mo; Yuan Shi; Zhijia Yin; Hong Li; Lin Sun (Food Chemistry, 2025)

Complexation-precipitation synthesis of high surface area PbO/rice husk-based activated carbon composites for ultra-long-life lead‑carbon battery anodes - Jiecai Li; Yupeng Wu; Zizhun Wang; Qilong Wang; Zhiqiang Liu; Qinwen You; Xin Ding; Yang Sun; Tangjun Wang; Haibo Lin; Nan Lin (Chemical Engineering Journal, 2025)

The effect of construction measures on the seismic performance of a frame-infilled wall with fabricated constructional column - Shucheng Yuan; Haifeng Lin; Haibo Luo; Zhanyuan Zhu; Zuyin Zou; Wei Liang; Zhuoying Wang; Bing Ma; Jinxin Yao; Qichao Zhang; Jiangfeng Dong; Hwa Kian Chai (Bulletin of Earthquake Engineering, 2025)

Organic matter accelerated microbial iron reduction and available phosphorus release in reflooded paddy soils - Xipeng Liu; Yuchen Shu; Kejie Li; Haotian Wang; Qingfang Bi; Haibo Wang; Chengliang Sun; Xianyong Lin (Soil Ecology Letters, 2025)

High-entropy perovskite embedded in carbon-based catalyst toward peroxymonosulfate activation to degrade Rhodamine B: Performance and mechanism insights - Zihao Chen; Xingqi Huang; Yanjun Zuo; Haibo Wang; Wenming Chen; Lingce Kong; Xiaoyan Lin (Water Research, 2025)

Hot-pressing-assisted fabrication of high-lignin-content and self-crosslinked strong adhesives - Li Yan; Haibo Liu; Ruonan Wang; Lin Dai; Zhanhui Yuan; Chuanling Si (Chemical Engineering Journal, 2025)

Histone lactylation-augmented IRF4 is implicated in arsenite-induced liver fibrosis via modulating Th17 cell differentiation - Weiyong Chen; Peiwen Wang; Yan Xie; Daxiao Xie; Hailan Wang; Ning Bu; Jiaheng Lin; Meng Wu; Haibo Xia; Cheng Cheng; Yuanzhong Zhou; Qizhan Liu (Chemico-Biological Interactions, 2025)

H4K12 lactylation-regulated NLRP3 is involved in cigarette smoke-accelerated Alzheimer-like pathology through mTOR-regulated autophagy and activation of microglia - Hailan Wang; Haibo Xia; Jun Bai; Zhongyue Wang; Yue Wang; Jiaheng Lin; Cheng Cheng; Weiyong Chen; Jingshu Zhang; Qingbi Zhang; Qizhan Liu (Journal of Hazardous Materials, 2025)

Ratiometric fluorescence analysis of tetracycline by dual-ligand europium-based metal-organic framework - Yating Zhong; Keying Zhang; Xinru Wang; Haibo Liang; Ying Yu; Manli Guo; Yujuan Cao; Bixia Lin (Food Chemistry, 2025)

Accelerated removal and mechanism of tetracycline from water using immobilized bacteria combined with microalgae - Jinli Wang; Xiangnan Chen; Haibo Sun; Xueying Li; Qiang Lu; Pufeng Qin; Yang Yang; Dengni Lai; Lin Luo; Xin Peng; Yuan Yang; Zhibin Wu (Journal of Environmental Chemical Engineering, 2025)

A haplotype-resolved genome assembly of tetraploid Medicago sativa ssp. falcata - Wanying Li; Xuanzhao Li; Wei Li; Haibo Yang; Diandian Guo; Ting Guo; Yingying Meng; Qiang He; Hao Lin; Huilong Du; Lifang Niu (Science China Life Sciences, 2025)

Branch-Leaf ZrO2@SiC@WS2 fibers as outstanding microwave absorber with high-temperature tolerance - Yongzhen Ma; Ying Lin; Yan Cheng; Zhixin Cai; Yanlong Ma; Binglong Zheng; Hongwei Zhou; Haibo Yang (Chemical Engineering Journal, 2025)

Fluorescent biosensor for lead ion detection based on GR-5 DNAzyme and self-hybridization chain reaction - Min Li; Huanxi Chen; Yu Zhang; Yuxin Cheng; Fengyi Lin; Haibo Wang; Jianyuan Dai (Analytica Chimica Acta, 2025)

Biocontrol mechanisms of antagonistic yeasts on postharvest fruits and vegetables and the approaches to enhance the biocontrol potential of antagonistic yeasts - Fangfang Wu; Haibo Wang; Yankun Lin; Shun Feng; Xinguo Li (International Journal of Food Microbiology, 2025)

Oxygen influences in vitro assessment for phenolic compounds: Digestive stability, α-glucosidase inhibitory activity and bioavailability - Yi Wang; Ruge Lin; Laiming Zhang; Suqing Lan; Xingqian Ye; Haibo Pan; Shiguo Chen (Food Chemistry, 2025)

Surviving the heat: The homeostatic regulation mechanism of endangered Brachymystax tsinlingensis - Zhenlu Wang; Huan Ye; Peng Liu; Shaoqing Lin; Yizhou Wang; Qiong Zhou; Haibo Jiang; Jian Shao (Journal of Thermal Biology, 2025)

Establishment of human minor salivary gland organoids in laminin-GelMA hydrogel from healthy individuals and Sjögren’s disease patients - Enhang Lu; Jiaying Qian; Wei Liang; Haibo Xiang; Pengbing Ding; Mengying Jin; Zhiyu Lin; Yujie Chen; Zheng Wang; Xin Huang; Zhixuan Sun; Bolin Pan; et al. (Chemical Engineering Journal, 2025)

PupaNet: A versatile and efficient silkworm pupae (Bombyx mori) identification tool for sericulture breeding based on near-infrared spectroscopy and deep transfer learning - Haibo He; Hua Huang; Shiping Zhu; Lunfu Shen; Zhimei Lv; Yongkang Luo; Yichen Wang; Yuhang Lin; Liang Gao; Benhua Xiong; Fangyin Dai; Tianfu Zhao (Computers and Electronics in Agriculture, 2024)

π-π conjugated PDI supramolecular regulating the photoluminescence of imine-COFs for sensitive smartphone visual detection of levofloxacin - Xiaolong Hu; Haibo Sun; Yi Jiang; Xiang Xiao; Yunshan Liang; Ming Lei; Yuan Yang; Jiachao Zhang; Pufeng Qin; Lin Luo; Zhibin Wu (Food Chemistry, 2024)

Parkin deficiency exacerbates particulate matter-induced injury by enhancing airway epithelial necroptosis - Yuting Lin; Meiyu Quan; Xibin Wang; Wanqi Miao; Haibo Xu; Baiqi He; Bin Liu; Yanxia Zhang; Yijing Chen; Binqian Zhou; Mengying Xu; Li Dong; et al. (Science of The Total Environment, 2024)

Targeted quantitative metabolomic and flavor objective quantification technique reveal the impact mechanism of shaking on black tea quality and non-volatile metabolites - Jinjin Wang; Lichi Qu; Ziming Yu; Yongwen Jiang; Chengfa Yu; Xizhe Zhu; Qingju Lin; Linchi Niu; Yaya Yu; Qing Lin; Yan Shang; Haibo Yuan; et al. (Food Chemistry, 2024)

Optimized energy storage performances via high-entropy design in KNN-based relaxor ferroelectric ceramics - Minquan Wang; Ying Lin; Binglong Zheng; Qibin Yuan; Haibo Yang (Chemical Engineering Journal, 2024)

Theoretical and numerical methods for predicting the structural stiffness of unbonded flexible riser for deep-sea mining under axial tension and internal pressure - Haibo Sun; Yingying Wang; Lusheng Jia; Zeqing Lin; Hao Yu (Ocean Engineering, 2024)

Achieving efficient electromagnetic absorption in multifunctional carbon nanotube aerogels by manipulating radialized network structure - Zhixin Cai; Haibo Yang; Hongwei Zhou; Ying Lin; Yan Cheng; Qibin Yuan (Chemical Engineering Journal, 2024)

VfLRR-RLK1 benefiting resistance to Fusarium oxysporum reveals infection and defense mechanisms in tung tree - Haibo Wu; Wanzhen Mo; Yanli Li; Lin Zhang; Yunpeng Cao (Physiology and Molecular Biology of Plants, 2024)

Battery recycling models selection and contractual incentives: From an information sharing perspective - Lin Feng; Mengru Qu; Adolf K.Y. Ng; Peng Jia; Haibo Kuang (Journal of Cleaner Production, 2024)

Combined dilute alkali and milling process enhances the functionality and gut microbiota fermentability of insoluble corn fiber - Qing Jin; Yiming Feng; Xavier Cabana-Puig; Tran N. Chau; Ronnie Difulvio; Dajun Yu; Anyang Hu; Song Li; Xin M. Luo; Jactone Ogejo; Feng Lin; Haibo Huang (Food Chemistry, 2024)

Epigallocatechin-3-gallate stabilizes aqueous curcumin by generating nanoparticles and its application in beverages - Ruge Lin; Yi Wang; Huan Cheng; Xingqian Ye; Shiguo Chen; Haibo Pan (Food Chemistry, 2024)

Urea cycle promotion via ammonia-upregulated CPS1 is involved in arsenite-induced pulmonary fibrosis through enhancing collagen synthesis - Daxiao Xie; Peiwen Wang; Weiyong Chen; Jiaheng Lin; Meng Wu; Yue Wang; Haibo Xia; Cheng Cheng; Fuping Ye; Binafsha Manzoor Syed; Qizhan Liu (Chemico-Biological Interactions, 2024)

An Updated Review on Self-Healing Barrier Materials with Potential Application in Contaminated Soil / Groundwater Risk Control - Fuhao Fan; Haibo Li; Ying Lin; Yang Liu; Wei Yu; Yingying Wu (Water, Air, & Soil Pollution, 2024)

Stenotrophomonas maltophilia contributes to smoking-related emphysema through IRF1-triggered PANoptosis of alveolar epithelial cells - Haibo Xia; Jiaheng Lin; Yue Wang; Jinyan Yu; Hailan Wang; Cheng Cheng; Yi Yang; Tao Bian; Yan Wu; Qizhan Liu (Environmental Pollution, 2024)

Theory-guided unraveling of the mechanism underlying Cu1.0/Mn1.0-ZnO with dual reaction centers for enhanced peroxymonosulfate activation - Kaixuan Wang; Haibo Li; Xiaofei Qin; Ting Ma; Lin Zhu; Chenxi Zhang; Wei Yu; Xulun Zhou (Environmental Research, 2024)

A Pollution Barrier Self-Healing Material: Investigating the Effect of Individual Components on Its Performance and Determining Optimal Ratios and Healing Compositions - Fuhao Fan; Haibo Li; Liuyu Song; Ying Lin; Xiaofei Qin; Yang Liu; Sihan Li; Wei Yu; Yingying Wu (Water, Air, & Soil Pollution, 2024)

The effect of reflux ratio on sulfur disproportionation tendency in anaerobic baffled reactor with the heterotrophic combining sulfur autotrophic processes under high concentration perchlorate stress - Guiyang Cheng; Denghui Chen; Daohong Zhang; Haibo Li; Kang Du; Lin Zhang (Environmental Science and Pollution Research, 2024)

Ornidazole degradation by PMS activated by Co-Zr-TiO2 with abundant oxygen vacancies: Performance, mechanism and degradation pathway - Xiaofei Qin; Haibo Li; Kaixuan Wang; Yang Liu; Liuyu Song; Ying Lin; Fuhao Fan; Sihan Li; Ting Ma (Process Safety and Environmental Protection, 2024)

Pt-Zn clusters encapsulated in hierarchical MFI zeolite for efficient propane dehydrogenation - Jinyang Lu; Zhikang Xu; Yuanyuan Yue; Xiaojun Bao; Minggui Lin; Haibo Zhu (Chemical Engineering Journal, 2024)

Boosting decarboxylation of monomethyl adipate coupling to dimethyl sebacate through Pt electrode at high current density - Linchuan Cong; Yupeng Wu; Nan Lin; Xinxin Li; Fangbing Liu; Fuyu Han; Jin Yang; Ciduo Wang; Haibo Lin (Chemical Engineering Journal, 2024)

Modeling the long-term transport and fate of oil spilled from the 2021 A Symphony tanker collision in the Yellow Sea, China: Reliability of the stochastic simulation - Ruichen Cao; Zengrui Rong; Haibo Chen; Yi Liu; Lin Mu; Xianqing Lv (Ocean Modelling, 2023)

Solar wind dynamic pressure enhancements in upstream region near Mars - Dan Zhao; Jianpeng Guo; Yichun Hong; Weiduo Meng; Hui Huang; Haibo Lin; Xianghan Wang; Yan Chen; Linxia He; Yong Wei; Libo Liu (Icarus, 2023)

Acetylation at the O-6 position of t-Glc improved immunoactivity of α-1,6-glucan from longan by additionally activating Dectin-1 and CD14 receptors - Lin Liu; Haibo Lan; Yao Wang; Lei Zhao; Xuwei Liu; Zhuoyan Hu; Kai Wang (Carbohydrate Polymers, 2023)

IL-9-Producing Th9 Cells Participate in the Occurrence and Development of Iodine-Induced Autoimmune Thyroiditis - Yiwen Li; Hao Liu; Chengyan He; Yawen Lin; Lei Ma; Haibo Xue (Biological Trace Element Research, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

An Experimental Investigation into the Feasibility of a DC Hybrid Power Plant for a Northern Sea Route Ship - Yi Zhou; Kayvan Pazouki; Rose Norman; Haibo Gao; Zhiguo Lin (Journal of Marine Science and Engineering, 2023)
Increasingly, the melting of Arctic ice due to global warming has provided opportunities for commercial shipping between Asia and Europe. Given the vulnerability of the Arctic environment, especially due to emissions of short-lived pollutants from shipping activities, a more effective propulsion system with a comprehensive control strategy is required to reduce fuel consumption, thus potentially mitigating the impacts of shipping activities on the northern sea route (NSR). In this paper, a shipboard DC hybrid system powered by a combination of diesel generator sets and batteries is proposed and analysed in terms of its application on a ship in the NSR. The specific fuel consumption and various losses in the power sources were analysed to develop an efficiency-optimisation control strategy for the proposed DC hybrid power system. To evaluate the performance of the hybrid power system with the proposed optimisation control strategy, lab-scale experiments have been conducted in the Shanghai Marine Diesel Engine Research Institute to compare the proposed system with a conventional hybrid system. The experimental results indicate that the proposed DC hybrid power plant with the energy optimisation control contributes a 5.35% fuel saving compared with the DC fixed-speed diesel electric configuration during a scaled-down NSR scenario.

Can port systems be enhanced by government promotion? The case of port cooperation along the maritime silk road - Lin Feng; Xiaodong Li; Adolf K.Y. Ng; Peng Jia; Haibo Kuang; Xingxing Zhang (Ocean & Coastal Management, 2023)

Enhanced electron channel via the interfacial heterotropic electric field in dual S-scheme g-C3N4/WO3/ZnS photocatalyst for year-round antibiotic degradation under sunlight - Haibo Sun; Pufeng Qin; Jiayin Guo; Yi Jiang; Yunshan Liang; Xiaomin Gong; Xin Ma; Qing Wu; Jiachao Zhang; Lin Luo; Zhibin Wu (Chemical Engineering Journal, 2023)

Strategies for controlling gas evolution reactions to boost the divergent paired electrochemical upgrading of furfural in acidic environment - Xinxin Li; Linchuan Cong; Yupeng Wu; Nan Lin; Fangbing Liu; Deyuan Xin; Fuyu Han; Jin Yang; Weitong Chen; Haibo Lin (Chemical Engineering Journal, 2023)

Insights into the interfacial structure of Cu/ZrO2 catalysts for methanol synthesis from CO2 hydrogenation: Effects of Cu-supported nano-ZrO2 inverse interface - Yangzhi Xu; Maolin Wang; Zhiwei Xie; Dong Tian; Guan Sheng; Xin Tang; Haibo Li; Yichao Wu; Chuqiao Song; Xiaofeng Gao; Siyu Yao; Ding Ma; et al. (Chemical Engineering Journal, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Transcriptional repressor AGL79 positively regulates flowering time in Arabidopsis - Haibo Yang; Pengcheng Zhang; Diandian Guo; Na Wang; Hao Lin; Xingchun Wang; Lifang Niu (Journal of Plant Physiology, 2023)

Superior efficiency hydrogen peroxide production in acidic media through epoxy group adjacent to Co-O/C active centers on carbon black - Jili Yuan; Hao Yin; Xin Ge; Ronglan Pan; Caijuan Huang; Dechao Chen; Lin Hu; Haibo Xie (Chemical Engineering Journal, 2023)

Ecological engineering induced carbon sinks shifting from decreasing to increasing during 1981–2019 in China - Xiaojuan Xu; Jing Liu; Fusheng Jiao; Kun Zhang; Xin Ye; Haibo Gong; Naifeng Lin; Changxin Zou (Science of The Total Environment, 2023)

Performance and mechanism of GO removal by gypsum from aqueous solution - Ping Jiang; Guanzhong Zhou; Cuihong Li; Yanfei Yu; Lin Zhou; Haibo Kang (Environmental Science and Pollution Research, 2023)

Diverse metavolcanic sequences in the Cambrian accretionary complex at the Pamir Syntax: Implications for tectonic evolution from Proto-Tethys to Paleo-Tethys - Xiao-Qiang Liu; Chuan-Lin Zhang; Haibo Zou; Xian-Tao Ye (Journal of Asian Earth Sciences, 2023)

Electrosprayed thin film nanocomposite polyamide nanofiltration with homogeneous distribution of nanoparticles for enhanced separation performance - Yingyao He; Jianqiang Wang; Xinyu Fu; Haibo Lin; Weilin Zhang; Xiao Wang; Fu Liu (Desalination, 2023)

Mechanically strong and biodegradable holocellulose films prepared from Camellia oleifera shells - Haibo Long; Jin Gu; Jianchun Jiang; Litao Guan; Xiuyi Lin; Weiwei Zhang; Chuanshuang Hu (Carbohydrate Polymers, 2023)

The resting-state topological organization damage of language-related brain regions in post-stroke cognitive impairment - Sirui Wang; Bo Rao; Guofu Miao; Xin Zhang; Jun Zheng; Junbin Lin; Minhua Yu; Xiaoli Zhou; Haibo Xu; Weijing Liao (Brain Imaging and Behavior, 2022)

Sensitivity analysis of weather research and forecasting (WRF) model output variables to the thunderstorm lifecycle and its application - Haibo Huang; Caiyan Lin; Yangquan Chen (Natural Hazards, 2022)

An implementation framework of blockchain-based hazardous waste transfer management system - Guanghan Song; Yujie Lu; Haibo Feng; Han Lin; Yang Zheng (Environmental Science and Pollution Research, 2022)

Micro-/Meso-Scale Distinction and Horizontal Migration of Tintinnid (Ciliophora: Tintinnida) Assemblages in Three Regions Around the North Pacific Ocean - Meiping Feng; Shiquan Lin; Wuchang Zhang; Chunsheng Wang; Hongbin Liu; Shunyan Cheung; Haibo Li; Michael R. Stukel; John Paul Irving; Na Li (Frontiers in Marine Science, 2022)
We explored the relationships among different tintinnid populations on micro-, meso-, and basin-scales from three regions across the Pacific Ocean, including the Costa Rica Dome (CRD) in the Eastern Pacific Ocean, the Celebes Sea (CS), and the Tokara Strait (TS) in the Western Pacific Ocean. We quantified the species occurrence, vertical and biogeographic distribution patterns, and morphological parameters of tintinnid assemblages. A total of 46 tintinnid species were observed, with more than half (63.0%) in common among the three areas, accounting for 97.1% of the total abundances. The numerically abundant forms remained more or less the same set of species in the three areas. However, community structure analyses, in terms of species, lorica oral diameter (LOD) size classes, and genera, revealed clear distinctions among different regions, as well as among different water depths. A Lagrangian simulation of passive dispersal in ocean currents across the Pacific Ocean, supported the hypothesis that greater similarity between tintinnid populations in the CS and TS (relative to CRD), was related to ocean circulation linkages between the populations. A latitudinal decline of tintinnid species richness was observed, mainly as a result of a decline of redundant species and warm-water species in colder areas. These data provide information unique insight into population variability of microzooplankton communities on micro- to meso- and even large scales in the world oceans.

Stocks and losses of soil organic carbon from Chinese vegetated coastal habitats - Chuancheng Fu; Yuan Li; Lin Zeng; Haibo Zhang; Chen Tu; Qian Zhou; Kuanxu Xiong; Jiaping Wu; Carlos M. Duarte; Peter Christie; Yongming Luo (Global Change Biology, 2021)
Global vegetated coastal habitats (VCHs) represent a large sink for organic carbon (OC) stored within their soils. The regional patterns and causes of spatial variation, however, remain uncertain. The sparsity and regional bias of studies on soil OC stocks from Chinese VCHs have limited the reliable estimation of their capacity as regional and global OC sinks. Here, we use field and published data from 262 sampled soil cores and 181 surface soils to report estimates of soil OC stocks, burial rates and losses of VCHs in China. We find that Chinese mangrove, salt marsh and seagrass habitats have relatively low OC stocks, storing 6.3 ± 0.6, 7.5 ± 0.6, and 1.6 ± 0.6 Tg C (±95% confidence interval) in the top meter of the soil profile with burial rates of 44 ± 17, 159 ± 57, and 6 ± 45 Gg C/year, respectively. The variability in the soil OC stocks is linked to biogeographic factors but is mostly impacted by sedimentary processes and anthropic activities. All habitats have experienced significant losses, resulting in estimated emissions of 94.2–395.4 Tg CO 2 e (carbon dioxide equivalent) over the past 70 years. Reversing this trend through conservation and restoration measures has, therefore, great potential in contributing to the mitigation of climate change while providing additional benefits. This assessment, on a national scale from highly sedimentary environments under intensive anthropogenic pressures, provides important insights into blue carbon sink mechanism and sequestration capacities, thus contributing to the synchronous progression of global blue carbon management.

Grazing by microzooplankton and copepods on the microbial food web in spring in the southern Yellow Sea, China - Yuan Zhao; Yi Dong; Haibo Li; Shiquan Lin; Lingfeng Huang; Tian Xiao; Gerald Gregori; Li Zhao; Wuchang Zhang (Marine Life Science & Technology, 2020)
Assessment of microzooplankton and copepods grazing pressure on picoplankton is a key requirement for resolving the microbial food web efficiency. Although microzooplankton grazing on picoplankton has been extensively studied, the impact of microzooplankton on different groups of picoplankton, i.e., heterotrophic bacteria, Synechococcus and picoeukaryotes have rarely been compared. Furthermore, in the very few existing studies there is no consistent evidence of an enhancing or restraining effect of copepods on picoplankton. More studies are needed to improve our understanding of the influence of microzooplankton and copepod on picoplankton. Dilution incubations and copepod addition incubations were performed during a cruise to the southern Yellow Sea on May 16–29, 2007. The bulk grazing of microzooplankton and the calanoid copepod Calanus sinicus on phytoplankton, flagellates and picoplankton was estimated. Stations were divided into either eutrophic or oligotrophic according to the nutrient and biological parameters. Picoplankton comprised a large part of the diet of microzooplankton in the central oligotrophic area, while phytoplankton was the main food of microzooplankton in the coastal eutrophic area. In the central oligotrophic area, microzooplankton preferred grazing on Synechococcus . After copepod addition, ciliate abundance decreased while Synechococcus abundance increased (382%, 64% and 64% at three experimental stations, respectively), indicating strong grazing pressure of microzooplankton on Synechococcus . Our results suggest that Synechococcus might be an essential carbon source the planktonic food web in the oligotrophic waters of southern Yellow Sea.

Influence of simulating deep-sea environmental factors on cathodic performance of seawater battery - Yonghong Lu; Lulu Yang; Yue Zhang; Qing Zhao; Lin Sang; Fei Ding; Haibo Xu (Journal of Oceanology and Limnology, 2020)

Impacts of Age and Expansion Direction of Invasive Spartina alterniflora on Soil Organic Carbon Dynamics in Coastal Salt Marshes Along Eastern China - Qi Xiangzhen; Liu Huiyu; Lin Zhenshan; Liu Xiang; Gong Haibo (Estuaries and Coasts, 2019)

Combined Effects of Global Climate Suitability and Regional Environmental Variables on the Distribution of an Invasive Marsh Species Spartina alterniflora - Huiyu Liu; Xiangzhen Qi; Haibo Gong; Lihe Li; Mingyang Zhang; Yufeng Li; Zhenshan Lin (Estuaries and Coasts, 2019)

Eburicoic acid from Laetiporus sulphureus (Bull.:Fr.) Murrill attenuates inflammatory responses through inhibiting LPS-induced activation of PI3K/Akt/mTOR/NF-κB pathways in RAW264.7 cells - Junzhi Wang; Pan Zhang; Haibo He; Xinxin Se; Wenjun Sun; Beiyan Chen; Lin Zhang; Ximing Yan; Kun Zou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Tetrasomic inheritance pattern of the pentaploid Solanum chacoense (+) S. tuberosum somatic hybrid (resistant to bacterial wilt) revealed by SSR detected alleles - Lin Chen; Xianpu Guo; Haibo Wang; Conghua Xie; Xingkui Cai; Li He; Jun Zhou; Jun Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

CD14 −159C/T polymorphism contributes to the susceptibility to tuberculosis: evidence from pooled 1,700 cases and 1,816 controls - Ruifen Miao; Haibo Ge; Lin Xu; Fei Xu (Molecular Biology Reports, 2014)

An analytical algorithm with a wave age factor for altimeter wind speed retrieval - Yongcun Cheng; Qing Xu; Yuguang Liu; Hui Lin; Peng Xiu; Xiaobin Yin; Haibo Zong; Zengrui Rong (International Journal of Remote Sensing, 2008)

The South Pacific Subtropical Mode Water in the Tasman Sea - Haibo Hu; Qinyu Liu; Xiaopei Lin; Wei Liu (Journal of Ocean University of China, 2007)